Pembentukan Karakter Peserta Didik Melalui Manajemen Budaya Sekolah di Tingkat Sekolah Dasar - Rahayu, Sayekti Puji; Roesminingsih, Erny; Hariyati, Nunuk (Universitas Negeri Surabaya, 2022)
The character of students can be formed through school culture. It is important for education units to implement school culture management as an effort to build the character of students. The aims of this research is to find out the forms of the planning, organizing, implementing, and supervising school culture.The type of this research is qualitative research and the data obtained through in-depth interviews, observations, and documentation studies. Furthermore, the data were analyzed by applying the triangulation technique. The results of the research are: 1) School culture planning through formulation the school’s vision, mission, goals, arranging an education unit level curriculum, educational programs, and the teachers arrange the learning tools; 2) Organizing school culture through by arranging an organizational structure, division of tasks, coordination meetings, and socialization activities; 3) The implementation of the school culture through habituation activities and giving examples; 4) Supervision of school culture is carried out directly on the behavior of the students, reward, punishment, and report cards descriptions, 5) The characters of the students that be formed are religious, discipline, confident, independent, honest, helpful, empathetic, tolerance, creative, cooperation, courtesy, love for the nation, respect to teachers and parents. School culture that was managed can shape the character of students.